Mathematical models for effectiveness of contact tracing on the onset of an epidemic - (:unkn) unknown (My University, 2015)
Paper presented at Strathmore International Mathematics Research Conference on July 23 - 27, 2012
Paper presented at Strathmore International Math Research Conference on July 23 - 27, 2012
Keywords: Mathematical Models; Mathematical models and epidemiology